A Semiotic Analysis on Signs Used on Tingkuluak Traditional Clothes of Koto Gadang - Zulhantiar, Putri Annisa; Zein, Mutiara; Mawarni, Nidiya; Angin, Alemina Br. Perangin (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This study conducts a semiotic analysis of the signs embedded in Tingkuluak Koto Gadang, a traditional headpiece worn by Minangkabau women in Indonesia. Employing Charles Sanders Peirce's triadic model of semiotics, the research examines how motifs, colors, and ornaments function as signs to convey cultural meanings. The qualitative case study approach involved direct observation, visual documentation, and interviews with cultural experts to identify and interpret the semiotic elements in Tingkuluak Koto Gadang. The analysis revealed ten signs categorized into six types: Sinsign, Legisign, Icon, Index, Symbol, and Decisign. Among these, Icon and Decisign were the most dominant, with three occurrences each. For instance, the color red and gold serve as Icons, symbolizing courage and prosperity, while floral motifs like Bunga and Akar Daun function as Decisigns, representing harmony and resilience. Other signs, such as the Padi motif (Symbol) and Rumbai Kotak (Index), reflect agricultural heritage and structured societal values, respectively. The findings underscore that Tingkuluak Koto Gadang is not merely decorative but a rich semiotic system encoding Minangkabau identity, social norms, and philosophical values. However, the study highlights a growing disconnect among younger generations, who increasingly perceive these garments as aesthetic rather than symbolic. This research contributes to cultural preservation by decoding the hidden meanings of traditional attire, emphasizing the need for educational initiatives to sustain this intangible heritage. It also demonstrates the efficacy of Peirce’s semiotic framework in analyzing non-verbal cultural texts, offering a model for future studies on traditional clothing and material culture